In Vitro Antioxidant, Anti-Inflammatory, and Digestive Enzymes Inhibition Activities of Hydro-Ethanolic Leaf and Bark Extracts of Psychotria densinervia (K. Krause) Verdc - Jean Romuald Mba; Djamila Zouheira; Hadidjatou Dairou; Fanta S. A. Yadang; Nfor Njini Gael; Lawrence Ayong; Jules-Roger Kuiate; Gabriel A. Agbor (Advances in Pharmacological and Pharmaceutical Sciences)
Psychotria densinervia hydro-ethanolic leaf extract (PHELE) and bark extract (PHEBE) were evaluated for antioxidant, anti-inflammatory, and inhibition of digestive enzymes activities. The antioxidant activity was characterized by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), total phenolic content (TPC), and total flavonoid content (TFC) assays. The anti-inflammatory activity was characterized by protein denaturation and antiproteinase tests, while the inhibition of the enzymes was assessed using α-amylase, α-glucosidase, lipase, and cholesterol esterase activities. PHELE presented low (p<0.001) IC50 (59.09 ± 5.97 μg/ml) for DPPH compared with ascorbic acid (71.78 ± 6.37 μg/ml) and PHEBE (115.40 ± 1.21 μg/ml). The IC50 of PHELE (262.4 ± 4.46 μg/ml) and PHEBE (354.2 ± 1.97 μg/ml) was higher (p<0.001) than that of catechin (33.48 ± 2.02 μg/ml) for ABTS. PHELE had high (p<0.001) FRAP (341.73 ± 21.70 mg CE/g) than PHEBE (150.30 ± 0.32 mg CE/g). PHELE presented (p<0.001) high TPC (270.05 ± 7.53 mg CE/g) and TFC (23.43 ± 0.032 mg CE/g) than PHEBE (TPC: 138.89 ± 0.91 and TFC: 20.06 ± 0.032 mg CE/g). PHELE showed antiprotein denaturation with IC50 (257.0 ± 7.51 μg/ml) (p<0.001) and antiproteinase activity (74.37 ± 1.10 μg/ml) lower than PHEBE (316.1 ± 6.02 μg/ml and 177.6 ± 0.50 μg/ml), respectively. Orlistat inhibited lipase (p<0.001) activity with IC50 (37.11 ± 4.39 μg/ml) lower than PHELE and PHEBE (50.57 ± 2.89 μg/ml and 62.88 ± 1.74 μg/ml, respectively). PHELE inhibited cholesterol esterase with IC50 (34.75 ± 3.87 μg/ml) lower than orlistat (54.61 ± 2.56) and PHEBE (80.14 ± 1.71 μg/ml). PHELE inhibited α-amylase IC50 (6.07 ± 4.05 μg/ml) lower than PHEBE (19.69 ± 6.27 μg/ml) and acarbose (20.01 ± 2.84 μg/ml). Acarbose inhibited α-glucosidase (p<0.001) activity with IC50 (4.11 ± 3.47 μg/ml) lower than PHELE (24.41 ± 2.84 μg/ml) and PHEBE (38.81 ± 2.46 μg/ml). PHELE presented better antioxidant, anti-inflammatory, and enzyme inhibition activity than PHEBE.